Effects of A site doping on the crystallization of perovskite films. Issue 3 (17th December 2020) - Zhang, Caiyi; Wang, Yanbo; Lin, Xuesong; Wu, Tianhao; Han, Qifeng; Zhang, Yiqiang; Han, Liyuan
Abstract : The effects of A site doping on the crystallization, including the morphology and crystallinity of the PbI2 layer, nucleation and growth, phase transition and crystal orientation. Abstract : Perovskite materials with ABX3 chemical formula have a high absorption coefficient, high mobility and low exciton binding energies, and thus are promising candidates for the next generation of photovoltaic devices. Doping various cations on the A site has been reported to be beneficial for improving the performance and stability of perovskite solar cells. However, the mixed cation compositions make the perovskite crystallization mechanism complicated. To better manipulate perovskite crystallization, it is essential to understand the effects of A site doping on the perovskite crystallization. Four influences of A site doping on the crystallization of perovskite films are reviewed in this paper: (1) the influences on the morphology and crystallinity of the PbI2 layer; (2) nucleation and growth; (3) phase transition; (4) crystal orientation. At the end, we suggest that the influence of A site doping on the performance and stability of perovskite solar cells should be further studied with the help of advanced in situ characterization methods, theoretical computation and machine learning.